The discovery of Neotropical Lepidosira (Collembola, Entomobryidae) and its systematic position. (21st July 2019) - Nunes, Rudy C.; Godeiro, Nerivânia N.; Pacheco, George; Liu, Shanlin; Gilbert, Marcus Thomas P.; Alvarez‐Valin, Fernando; Zhang, Feng; Bellini, Bruno C.
Abstract: We herein present the first reliable record of Lepidosira from Neotropical Region. Lepidosira neotropicalis sp. n. from Brazil is described and illustrated in detail, including its complete mitochondrial genome. We perform a Bayesian phylogenetic analysis to place the new species within the Entomobryidae, and at the same time to test previous contrasting hypotheses on Lepidosira position within the Entomobryinae versus Seirinae for the first time. Phylogenetic analyses were based on one mitochondrial and two nuclear genes, Cytochrome Oxidase subunit I, 18S ribosomal RNA and 28S ribosomal RNA, respectively. Lepidosira neotropicalis sp. n. resembles L. sundana Yoshii and Suhardjono and L. nigropunctata (Nguyen) in dorsal chaetotaxy of abdominal segments I and II, but differs from all other species by the combination of head (dorsally and ventrally) and dorsal trunk chaetotaxy, plus empodial complex morphology. Our phylogenetic analyses support the placement of Lepidosira within Entomobryinae, as the sister group of Lepidocyrtoides . Overall, our revision enables a more objective diagnosis to Lepidosira and suggests that the genus is in need of a full revision due to its variable morphology, and lack of data needed to evaluate its monophyly. Finally, we provide an identification key for Neotropical genera of Entomobryinae.